A variação discursiva de e, aí e então na fala e na escrita de alunos pessoenses do ensino fundamental: uma proposta de material para sala de aula - Silva, Priscila Sheila de Medeiros da (2023)
This work concerns the discourse variation of the retroactive-propeller sequence connectors E, AÍ and ENTÃO, in narrative texts written by 31 sixth-grade students from Escola Estadual Isabel Maria das Neves. After investigating the intercurrence of speaking over writting (Marcuschi, 2004; Cagliari, 2010) on the students’s records, the present work aims to propose instructional materials that help the students comprehend this variation as well as the possible scenarios in which each variable occurs, minimizing their difficulty in using the mentioned sequence connectors on formal writting. The primary hypothesis states that students express typical usages of less-supervised speech in formal writting and that a variationist reflection on the employment of these connectors in several communicative situations might guide the students through usages that are more conscious and suitable for specific sociointeractive demands. For this purpose, we review a few studies regarding the theme of sequenciation (Tavares, 2003; Silva, 2013; Vieira, 2016), not only from a theoretical approach but also from a pedagogical perspective; we enter the instructional class book, highlighting both positive and negative points with respect to the treatment given to language in the collection; and we compare, grounded on the theoretical-methodological contribution of Variationist Sociolinguistics (Weinreich, Labov e Herzog, 1968; Labov, [2008] 1972), the use of E, AÍ and ENTÃO on students’s oral narratives and written tales, by verrifying the influence of the linguistics variables sequenciation subfunctions, articulation levels, genre and verb aspect, and the social variables, sex and school class, on the variation establishment. We therefore build multinomial logistics regression models on platform R, applying Mlogit function. We present the results of the retroactive-propeller sequenciation on the students’s oral and writting extracts, which show that AÍ is favored in intertopic environment and E is in turn favored in intratopic situation, in masculine sex, in writting texts and in the subfunctions finalization and introduction of effect. In view of the results and based on the principles of Educational Sociolinguistics (Bortoni-Ricardo, 2004), we propose a three-module didactic series of activities for promoting discussion about linguistics variation during class, by analysing and rewritting the students’s own productions and reflecting on the employment and the social avaliations of the use of sequence connectors in real language.